Match peak speed of elite male soccer players across a full season: The influence of playing position, competition, match outcome, and match location - Silva, H.; Nakamura, F. Y.; Gómez-Diaz, A.; Menezes, P.; Marcelino, R. (Kinesiology, 2025)
This study compared match peak speeds (MPS) across a full season considering different playing positions, competitions, match outcomes, and match locations. Thirty-one elite male soccer players were monitored during matches using global navigation satellite system devices. Independent mean differences [95% confidence intervals] were calculated for the investigated variable (MPS). Fullbacks reached higher MPS than central defenders (CD) (d=0.78 [0.56, 1.00]), central midfielders (CM) (d=-0.75 [-0.93, -0.57]) and forwards (d=-0.32 [-0.55, -0.08]); wide midfielders reached higher MPS than CD (d=0.66 [0.43, 0.90]) and CM (d=0.64 [0.45, 0.84]); and forwards reached higher MPS than CD (d=0.46 [0.22, 0.71]) and CM (d=0.41 [0.21, 0.62]). Higher MPS were reached during the National League than the National Cup (d=-0.38 [-0.58, -0.19]) and the Supercup (d=-0.57 [-1.09, -0.06]); higher MPS were reached during the State Cup than the National Cup (d=-0.32 [-0.55, -0.09]) and the Supercup (d=-0.57 [-1.12, -0.05]); and higher MPS were reached during the International Cup than the National Cup (d=0.26 [0.04, 0.48]). Higher MPS were reached during matches lost than won (d=0.19 [0.03, 0.35]). Playing position was the highest differentiator of MPS across a soccer season, underlining the importance of players` individualization when assessing MPS or when calculating normalized speed thresholds. MPS can also vary between competitions, especially if teams face lower division teams.